The house at Saltwater Point - Coble, Colleen (Nashville, Tennessee : Thomas Nelson, 2018)
"Ellie Blackmore is making a name for herself as a house flipper. But when her sister Mackenzie disappears, Ellie can't focus on anything but uncovering what happened. Her only clue is the bloodstain on the deck of Mackenzie's boat. Ellie knows her sister isn't on the best of terms with her ex-husband, Jason, but he wouldn't kill her--would he? Coast Guard intelligence officer Grayson Bradshaw believes Mackenzie fakedher own death after stealing a seized cocaine shipment. The problem is convincing Ellie, who seems to view him as the true enemy. Both Ellie and Grayson want truth, but truth--and family--is often more complex than it first appears."--
Includes discussion questions (page 325).
Keywords: Sisters -- Fiction; Missing persons -- Fiction; Romance fiction; Thrillers (Fiction)